2010
DOI: 10.1007/s11118-010-9199-4
|View full text |Cite
|
Sign up to set email alerts
|

Global Comparison Principles for the p-Laplace Operator on Riemannian Manifolds

Abstract: Abstract. We prove global comparison results for the p-Laplacian on a p-parabolic manifold. These involve both real-valued and vector-valued maps with finite p-energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…In the theorem below we demonstrate a global comparison principle for complete Riemannian manifolds with infinite volume whose geodesic flow is recurrent. Similar results can be found in [18], [14] and [6].…”
Section: Applicationssupporting
confidence: 89%
“…In the theorem below we demonstrate a global comparison principle for complete Riemannian manifolds with infinite volume whose geodesic flow is recurrent. Similar results can be found in [18], [14] and [6].…”
Section: Applicationssupporting
confidence: 89%
“…In [17], the authors take a first step in this direction by proving that a map u : M → N with finite p-energy and homotopic to a constant is constant provided M is p-parabolic and N Sect ≤ 0. Using Theorem 6 in the proof of their result, we easily obtain the following In [12], the authors apply the Kelvin-Nevanlinna-Royden criterion to obtain a vector valued version of their comparison theorem. In some sense this result is a further step in treating the problem of the uniqueness of p-harmonic representative.…”
Section: Applicationsmentioning
confidence: 99%
“…As a matter of fact, in their proof X is defined in such a way that the smoothness of u and v seems to be strictly necessary to do computations. In order to generalize their result, in the direction of Proposition 7, apparently assumption (12) can not be dropped. Nevertheless, in case |du|, |dv| ∈ L p and their L p -norms decay fast with respect to the volume in the A M,p sense, we obtain a similar result for non p-parabolic manifolds and for maps with low regularity.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[47] 6.3). In [15], I. Holopainen, S. Pigola and G. Veronelli showed that if u, v ∈ W 1,p loc (M) ∩ C 0 (M) satisfy ∆ p u ≥ ∆ p v weakly and |∇u| , |∇v| ∈ L p (M) , for p > 1, then u − v is constant provided M is connected, possibly incomplete, p-parabolic Riemannian manifold. They also discussed L q comparison principles in the non-parabolic setting.…”
Section: Introductionmentioning
confidence: 99%